Microbiota of the conjunctival sac of 120 healthy cats. (10th August 2018) - Büttner, Jessica Nina; Schneider, Marianne; Csokai, Jaqueline; Müller, Elisabeth; Eule, Johanna Corinna
Abstract: Objectives: To describe the bacterial and fungal microbiota of the conjunctiva and factors influencing these microbiota of healthy cats. To evaluate the antimicrobial resistance profile and discuss the use of appropriate antimicrobial drugs. Animals studied: One hundred and twenty healthy cats Procedures: Conjunctival samples with dry or premoistened swabs were obtained from both eyes and cultured for aerobic and anaerobic bacteria and fungi. In vitro bacterial, susceptibility testing was performed. The effects of age, sex, breed, season, living environment, and sample collection technique on the frequency and composition of microbial isolation were evaluated. Results: In 49 of 120 cats (40.8%) and 73 of 240 swabs (30.4%), microorganisms were isolated. Of the isolates, 71% (61/86) were Gram‐positive bacteria, 26% (22/86) were Gram‐negative bacteria, and 3% (3/86) were fungi. Staphylococcus felis (17/86; 19.8%) was the most commonly isolated species. Moraxella osloensis (5/86; 5.8%) was the most frequent Gram‐negative species. The season had a statistically significant influence ( P  = 0.04) on the frequency of isolation. The use of premoistened swabs increased the rate of Gram‐positive bacterial detection significantly ( P  = 0.03). The in vitro susceptibility testing showed high efficacy of chloramphenicol, gentamicin, pradofloxacin, and enrofloxacin. Conclusions: The isolated microbiota aligns with previous studies performed in other countries, although the microbiota of cats in the present study showed wider bacterial diversity, and more Gram‐negative species were isolated. Swab sampling should be performed with premoistened swabs. The topical antimicrobials gentamicin and chloramphenicol are suitable therapeutics for first‐line treatment.